FREKUENSI LATIHAN PLIOMETRIK (PUSH UP DAN PULL UP) TERHADAP PRESTASI MEMANAH - Hardi, Veny Juniarni (STKIP Pasundan, 2019)
This article aims to examine the extent of the influence of the frequency of plyometric exercises (push ups and pull ups) on archery achievements of 30 meters distance in the STKIP Pasundan Archery UKM students in Cimahi. The research method used in this study is the experimental method, while the population and samples used in the study are students who are members of the UKM (Student Activity Unit) Archery STKIP Pasundan Cimahi. For research instruments or data collection tools used is the instrument used is to test arrow shots to the  triangle target with a distance of 30 meters. The results of this study show that there is a significant effect of the frequency of plyometric exercises (push ups and pull ups) on archery achievements of 30 meters in distance from the UKM STKIP Pasundan Cimahi students. The calculation results show t = 6,703, p = 0,000 means significant. Thus the alternative hypothesis is accepted. This means that the frequency of plyometric exercises (push ups and pull ups) has a significant influence on archery achievements of 30 meters distance in the STKIP Pasundan Archery UKM students in Cimahi. The mean for the initial test and the final test shows a positive difference. Thus, there is a difference in archery achievements of 30 meters between before training and after training